2018
DOI: 10.1016/j.system.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality in medicine: How university medical students approach informative leaflets

Abstract: This study aims to analyse multimodality in medical leaflets to see how images and other semiotic modes combine with text-flow, adding meaning to the message and broadening the communicative spectrum. Traditionally, in the educational sphere, more importance has been given to text rather than to other semiotic modes but, in fact, writing is also a multimodal practice. In medicine, the visual becomes vital, whether accompanied by meaningful written text or not. The present study analyses 50 medical leaflets des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…16 Residents also emphasized the importance of multimodal educational opportunities which have been recently employed in many facets of medical education. 11,13 Importantly, this experience did not require a large expenditure of faculty time and resources. In addition, residents valued an opportunity to observe peers and receive instant, formative, and individualized feedback on a challenging skill.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…16 Residents also emphasized the importance of multimodal educational opportunities which have been recently employed in many facets of medical education. 11,13 Importantly, this experience did not require a large expenditure of faculty time and resources. In addition, residents valued an opportunity to observe peers and receive instant, formative, and individualized feedback on a challenging skill.…”
Section: Discussionmentioning
confidence: 98%
“…9 We chose to include multiple modalities of learning, as recent studies have shown that the integration of different modalities is both effective and preferred by learners. 10,11 We strove to create an evidence-based, adaptable, and application-oriented training program, and compared this to the existing communication curriculum at our institution using several different outcome measures. We initially explored how this curriculum impacted the patient experience.…”
Section: Introductionmentioning
confidence: 99%
“…Franceschi ( 2018 ) supported a multimodal approach to teaching medical English because communication does not only involve linguistic and cognitive capacity but also the ability to use a range of non-verbal elements. Belles-Fortuno ( 2018 ) explored the importance of multimodality in medical students’ learning products regarding the English for Health Sciences module. It was found that multimodality added further meaning and broadened the communicative spectrum of leaflets completed by the students.…”
Section: Literature Reviewmentioning
confidence: 99%